Evaluasi Program Pelatihan Project-Based Learning bagi Guru dengan Model Kirkpatrick - Reinhard Leonardo Paais; Sabirin (Kelola: Jurnal Manajemen Pendidikan, 2025)
This studi aims to evaluate the effectiveness of Project-Based Learning (PjBL) training for teachers using two levels of the Kirkpatrick Model: Reaction and Learning. The training is essential to equip teachers in meeting the demands of 21st-century education, where teachers serve as facilitators who encourage active student participation in meaningful learning. The research subjects consisted of 25 junior and vocational high school teachers from the Islamic Development Network Boarding School Solo who participated in the Project-Based Learning (PjBL) training. Data were collected through evaluation questionnaires (Reaction level) and pretest-posttest assessments (Learning level). The data were analyzed quantitatively. The evaluation at the Reaction level indicated that the training was rated very positively by participants, with an overall average score of 4.21. Four aspect are material relevance, facilitators, training methods, and facilities and media were rated as “Very Good.” Meanwhile, the aspects of training duration and participant engagement were rated as “Good.” At the Learning level, the results of a paired sample t-test showed a significant increase in participants' knowledge scores after the training (pretest mean = 50.20; posttest mean = 84.80; sig. 0.000 < 0.05). These results indicate that the training successfully enhanced teachers’ understanding of the concepts and implementation of Project-Based Learning (PjBL). Therefore, the Project-Based Learning (PjBL) training proved to be effective in improving teachers’ knowledge and received a positive response from participants. This evaluation provides a valuable foundation for developing more impactful and contextual teacher training programs, and supports the improvement of learning quality in schools.